APLIKASI KOMPRESI DATA MENGGUNAKAN METODE HUFFMAN STATIK PADA PERANGKAT MOBILE BERBASIS ANDROID - Heru Cahya Rustamaji; Mariani Mariani; Bambang Yuwono (Telematika, 2014)
Efficient use of bandwidth and memory into the main focus that must be considered in the process of data exchange. More and more data is stored, the greater the size of the data. One alternative that can be implemented is to reduce the size of the (compressed) data. In addition to the process of data transmission, compression is also useful in the data storage medium in the secondary. Compression aims to reduce the amount of data used to represent the contents of a text file, image, audio, and video without reducing the quality of the original data. Compression is done by reducing the number of bits needed to store or transmit the digital media. For data compression, one algorithm has a good performance is the type of the Huffman algorithm.In this study, the Static Huffman algorithm which is one technique that is lossless data compression. Static Huffman algorithm uses frequency/probability of occurrences of a symbol in a string as input and produce output in the form of a prefix code that encodes a string using the little bits of all possible binary prefix code that may be. Static Huffman algorithm implementation is aimed to compress the data so that the compressed data size is smaller than the size of the original data. So that the compressed data can be retrieved, then the decompression process. This application was made and in the making based on Android using Eclipse and the methodology GRAPPLE (Guidlines for Rappid Application Engineering). GRAPPLE is a process modeling in software development which emphasizes the actions carried out in a number of stages , each stage will result in products that work with object-oriented form.With applications of data compression with Huffman Static method in Android -based mobile devices, the data size becomes smaller so that it can speed up the process of delivery and storage. Compression using Huffman code would be optimal if the range of the character of the information is not too much despite the high frequency of occurrence and the size of the compression results obtained that the compression of each file depending on the characteristics of the file to be compressed. Keywords : Compression, Decompression, Static Huffman Algorithm, Lossless, Android